2020
DOI: 10.1097/brs.0000000000003738
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Probability of the Global Alignment and Proportion Score for the Development of Mechanical Failure Following Adult Spinal Deformity Surgery in Asian Patients

Abstract: Study Design. This is a multicenter retrospective review of 257 surgically treated consecutive ASD patients who had a minimum of five fused segments, completed a 2-year follow-up (53 ± 19 yrs, females: 236 [92%]). Objective. This study aimed to validate the predictive probability of the GAP score in an Asian ASD patient cohort. Summary of Background Data. The GAP score is a recently established risk stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Specifically, we observed an increased risk in PJF rates in severely disproportioned patients, which supports earlier work in this area. 12,17,26 Our findings are also aligned with those of Yagi et al, 27 which suggested that at 2 years postoperatively, GAP-SD patients were at greatest risk of complications, including PJF.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, we observed an increased risk in PJF rates in severely disproportioned patients, which supports earlier work in this area. 12,17,26 Our findings are also aligned with those of Yagi et al, 27 which suggested that at 2 years postoperatively, GAP-SD patients were at greatest risk of complications, including PJF.…”
Section: Discussionsupporting
confidence: 89%
“…Failure to define a thoracic alignment relative to lumbar alignment and using postural measures (eg, pelvic tilt or sagittal vertical axis) has likely contributed to the poor external validity of current alignment guidelines. [14][15][16][17][18] Our results redefine what should be considered a normal sagittal alignment and fill a critical knowledge gap. In our first aim and consistent with prior studies on sagittal balance, we found C2 tilt (also known as the Odontoid-Hip-Axis) had minimal variation and is an ideal measure of global sagittal balance.…”
Section: Discussionmentioning
confidence: 60%
“…However, PI explains only a fraction of the variation observed in normal lumbar lordosis. Furthermore, currently accepted alignment targets utilize postural measures (eg, pelvic tilt, sacral slope, or sagittal vertical axis) that are not directly modifiable in surgery, and none of the targets define a reliable method for alignment the thoracic spine, likely contributing to the poor external validity of current alignment guidelines 14–18…”
mentioning
confidence: 99%
“…First, we did not incorporate all the preventive procedures in the present analysis. Terminal rod contour, administration of bisphosphonate, type of orthosis, and cement augmentation of UIV+1 vertebra may also prevent the development of MF 17,21,31,32 . The vast majority of our patient cohort used Jewett braces and did not have bisphosphonates before or after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal rod contour, administration of bisphosphonate, type of orthosis, and cement augmentation of UIVþ1 vertebra may also prevent the development of MF. 17,21,31,32 The vast majority of our patient cohort used Jewett braces and did not have bisphosphonates before or after surgery. Additionally, in most of the procedures, the proximal tips of the rod were slightly over-bent (increased kyphosis) intraoperatively to decrease the chance of PJK, but we did not set a particular angle for the terminal contour of the rods.…”
Section: Discussionmentioning
confidence: 99%